Modern Economic Space in Polish Cities as a Symptom of Globalisation - Wdowicka, Magdalena (Quaestiones Geographicae, 2011)
Globalisation primarily embraces cities, which turn into major nodes of the global economic network. It is here that huge transnational corporations locate their operations, an intensive exchange of information takes place, and the largest global flows are registered. In seeking to adjust their economic and spatial structure to the requirements of the competitive global economy, cities undertake large-scale infrastructural investments and develop new forms of organisation of their economic space, including scientific-technological parks, high-quality spaces offering services to producers and business people, and modern office districts where the headquarters of global corporations, international economic organisations and financial institutions are concentrated. The aim of the paper is to analyse the resources of modern economic space in Polish cities in the age of dynamic globalisation, in particular such elements of this space as high-quality office stock and technological parks.